Sublesional use of bevacizumab (avastin) in recurrent laryngeal papillomatosis - Alcas Arce, Olenka (2016)
Recurrent laryngeal papillomatosis is a disease caused by the human papillomavirus that causes exophytic epithelial lesions. Currently, there is no definitive treatment, existing high recurrence of lesions. One of the promising alternatives is the use of KTP laser with bevacizumab. However, in our hospitals we do not have KTP, but only cold excision. We present a case of recurrent laryngeal papillomatosis treated with intralesional injections of bevacizumab (avastin) 16.5 mg/mL as adjuvant therapy to cold excision.